Unsaying God - Kars, Aydogan.
1 online resource (361 pages)
Keywords: Focusing on the first seven centuries of the Islamic intellectual history, Unsaying God examines the ways in which Muslim, and some Jewish, scholars negated what they said about God in order to indicate the limits of human thought on the absolute. Ardogan Kars argue that contemporary studies on apophasis and negative theology in Islam are strongly motivated by the challenges and demands of modernity, and tend to preserve European universalism in the language of pluralism.